Case report: A clinical case study of six patients with Chlamydia psittaci pneumonia - Dai, Jinmeng; Lian, Xue; Mo, Juanfen; Li, Xiaosi; Mo, Weiqiang; Wang, Haiqin; Jiang, Jianping (Frontiers in Cellular and Infection Microbiology, 2023)
Objective: To investigate the clinical features of Chlamydia psittaci pneumonia. Methods: We retrospectively analyzed the clinical data of 6 patients with Chlamydia psittaci pneumonia admitted to the Division of Pulmonary and Critical Care Medicine of The Second Hospital of Jiaxing from December 2021 to September 2022. Results: Six patients suffered from fevers, combined with cough in 5 cases, chest discomfort in 1 case, fatigue in 2 cases, and headache in 1 case. Laboratory findings showed that C-reactive protein (CRP), procalcitonin (PCT), and erythrocyte sedimentation rate (ESR) levels were elevated in all patients, with hypersensitive CRP (hCRP)≥70 mg/L in 6 cases and PCT≥0.5 ng/ml in 2 cases. Elevations were tested in 3 cases of lactate dehydrogenase (LDH) and 2 cases of transaminase. Chest computed tomography (CT) of most patients showed patchy high-density shadows with local consolidation, accompanied by air bronchogram sign and pleural effusion. After diagnosis by metagenomic next-generation sequencing (mNGS), all patients took a favorable turn following immediate adjustment of regimen to doxycycline-based therapy and active organ support, and the lesions would be completely disappeared, with favorable prognoses. Conclusion: Patients with Chlamydia psittaci pneumonia commonly present with sepsis and rapidly progressive disease. mNGS is critical for the early diagnosis of the disease, and favorable prognoses can be achieved as immediate adjustment of therapies after diagnosis.